Personality, media choice and political ideology: explaining ideological pluralism in China. Issue 4 (18th May 2020) - Ma, Deyong; Lewis, Orion A.
ABSTRACT: To what extent do personality traits and media exposure explain political ideology? How important is authoritarian information control in structuring political attitudes relative to individual-level factors? This article evaluates the sources of political ideology using survey data from over 10, 000 in internet users in China. Consistent with the literature, we find that both personality traits and media exposure are significantly associated with one's expressed ideological orientation. However prior individual-level personality traits appear to have a larger impact than information exposure and may cause citizens to self-select media information. This means that media effects have a differential impact on individuals, with authoritarian personalities being more prone to reinforce their views with propaganda. This research highlights important ways that personality mediates information exposure, helps to explain the micro-foundations that shape authoritarian control at an individual level, explains the efficacy of propaganda techniques, as well as the mechanisms of political pluralism under authoritarianism.